Gene Loss, Pseudogenization in Plastomes of Genus Allium (Amaryllidaceae), and Putative Selection for Adaptation to Environmental Conditions - Scobeyeva, Victoria A.; Artyushin, Ilya V.; Krinitsina, Anastasiya A.; Nikitin, Pavel A.; Antipin, Maxim I.; Kuptsov, Sergei V.; Belenikin, Maxim S.; Omelchenko, Denis O.; Logacheva, Maria D.; Konorov, Evgenii A.; Samoilov, Andrey E.; Speranskaya, Anna S. (Frontiers in Genetics, 2021)
Amaryllidaceae is a large family with more than 1,600 species, belonging to 75 genera. The largest genus—Allium—is vast, comprising about a thousand species. Allium species (as well as other members of the Amaryllidaceae) are widespread and diversified, they are adapted to a wide range of habitats from shady forests to open habitats like meadows, steppes, and deserts. The genes present in chloroplast genomes (plastomes) play fundamental roles for the photosynthetic plants. Plastome traits could thus be associated with geophysical abiotic characteristics of habitats. Most chloroplast genes are highly conserved and are used as phylogenetic markers for many families of vascular plants. Nevertheless, some studies revealed signatures of positive selection in chloroplast genes of many plant families including Amaryllidaceae. We have sequenced plastomes of the following nine Allium (tribe Allieae of Allioideae) species: A. zebdanense, A. moly, A. victorialis, A. macleanii, A. nutans, A. obliquum, A. schoenoprasum, A. pskemense, A. platyspathum, A. fistulosum, A. semenovii, and Nothoscordum bivalve (tribe Leucocoryneae of Allioideae). We compared our data with previously published plastomes and provided our interpretation of Allium plastome genes’ annotations because we found some noteworthy inconsistencies with annotations previously reported. For Allium species we estimated the integral evolutionary rate, counted SNPs and indels per nucleotide position as well as compared pseudogenization events in species of three main phylogenetic lines of genus Allium to estimate whether they are potentially important for plant physiology or just follow the phylogenetic pattern. During examination of the 38 species of Allium and the 11 of other Amaryllidaceae species we found that rps16, rps2, infA, ccsA genes have lost their functionality multiple times in different species (regularly evolutionary events), while the pseudogenization of other genes was stochastic events. We found that the “normal” or “pseudo” state of rps16, rps2, infA, ccsA genes correlates well with the evolutionary line of genus the species belongs to. The positive selection in various NADH dehydrogenase (ndh) genes as well as in matK, accD, and some others were found. Taking into account known mechanisms of coping with excessive light by cyclic electron transport, we can hypothesize that adaptive evolution in genes, coding subunits of NADH-plastoquinone oxidoreductase could be driven by abiotic factors of alpine habitats, especially by intensive light and UV radiation.